Torsional Strength Enhancement of Reinforced SCC Box Beams Using Internal Transverse Steel Bracing Technique - Hussein Abdallah, Muhammad; Hameed Aziz, Ali (International Journal of Engineering and Technology, 2018)
An experimental investigation was conducted, in this paper, to evaluate the torsional strength enhancement of reinforced self-compacting concrete box beams using internal transverse steel bracing technique. Seven beam specimens have dimensions of (2100x300x300mm) for length; width and depth respectively, were poured and tested under pure torsion. Three variables were adopted in the present study; presence or absence of steel bracings, type of steel bracing (X-Type and XW-Type) and a number of steel bracing (1,3 and 5). Accordingly, the tested beams are divided into three groups (based on steel bracing type), the first group consists of one non-strengthened beam specimen (reference), the second group consists of three beams strengthened by X-Type steel bracing; while, the third group consists of three beams strengthened by XW-Type steel bracing. It was found that the ultimate torque moment increased by about (14.4%, 34.3% and 59.2%) for beam specimens containing one, three and five X-Type steel bracing, respectively, in comparison with the reference beam. While, the ultimate torque moment increased by about (21.9%, 41.8% and 71.6%), for beam specimens containing one, three and five XW-Type steel bracing, respectively, in comparison with the reference beam. The paper concludes that the contribution was enhanced using the adopted technique.Â Â Â